2023
DOI: 10.1039/d3gc00440f
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of methanol and ethanol for 3,3′-bis(indolyl)methane synthesis through activation of peroxymonosulfate over a copper catalyst

Abstract: A greener and simple catalytic system is developed for the synthesis of biologically important 3,3′-Bisindolyl(methanes) (BIMs) using C1 and C2 alcohols as carbon source for the bridging methylene group. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The morphological description of CuO has already been provided in our previous study. 13 Hence, the same is not included in this work. The SEM image of ZnO provided in ESI† showed the 2D architecture of nanoplates and the same was observed in the TEM image (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The morphological description of CuO has already been provided in our previous study. 13 Hence, the same is not included in this work. The SEM image of ZnO provided in ESI† showed the 2D architecture of nanoplates and the same was observed in the TEM image (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 Moreover, in our recent study, it has been found that PMS can be easily activated by CuO in 3,3-bis(indolyl)methane formation, which complimented our present work of C2 trimer synthesis using CuO–ZnO/PMS as the catalytic system. 13…”
Section: Catalytic Studymentioning
confidence: 99%
See 2 more Smart Citations